Sustainable Management of Zakat Utilization - Akbar, Azzadhien; Zen, Muhammad (ITQAN: Journal of Islamic Economics, Management, and Finance, 2022)
The research was conducted by using a qualitative descriptive analysis method, which describes the analyzed data to draw further conclusions. This research was conducted by interviewing and observing the research object. Interviews were conducted with four resource persons consisting of 2 Depok City Baznas staff and 2 Depok Sejahtera program beneficiaries, while observations were made by looking at the website, social media, and Baznas Depok City brochures. Depok Sejahtera program has not been successful or not, because this program is still an ongoing process and will last for 3 years. If the three aspects which include increasing income, increasing religiosity, and social functioning can be achieved, it can be said that the Depok Sejahtera program is successful because it has achieved what the program was established for. In addition, there are also new discoveries in the form of changes in the scale of the distribution of zakat funds for productive activities (utilization) and consumptive activities (distribution) due to the Covid-19 pandemic.